2020
DOI: 10.2478/sjph-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Health-Related and Health-Related Quality of Life

Abstract: ObjectivesTo investigate the correlation between the four dimensions of Oral Health-Related Quality of Life (OHRQoL) and Health-Related Quality of Life (HRQoL) constructs in a dental patient population.MethodsA cross-sectional study carried out at HealthPartners, Minnesota, USA. This study is a secondary data analysis of available adult dental patients’ data. The instruments used to assess the OHRQoL and HRQoL constructs were the Oral Health Impact Profile–version with 49 items (OHIP-49) and Patient-Reported O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Several JIA-specific covariates related to disease activity and patient/parent-reported pain, and functional disability were associated with Child-OIDP in the present study. OHRQoL is recognized to be part of health-related quality of life [ 64 , 65 ], hence the association between patient/parent-reported covariates and OHRQoL was anticipated. In the present study biologic DMARDs, ongoing or ever used, were shown to be associated with impaired ECOHIS scores amongst the younger population with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…Several JIA-specific covariates related to disease activity and patient/parent-reported pain, and functional disability were associated with Child-OIDP in the present study. OHRQoL is recognized to be part of health-related quality of life [ 64 , 65 ], hence the association between patient/parent-reported covariates and OHRQoL was anticipated. In the present study biologic DMARDs, ongoing or ever used, were shown to be associated with impaired ECOHIS scores amongst the younger population with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study are the inclusion of participants with different edentulism durations and the relatively small sample size (which allowed only a pilot study to be conducted on the dimensionality). Further research should be directed towards performing the CFA on new samples from each country and towards the possible exclusion or inclusion of some new items in the OHIP-EDENT questionnaire ( 2 , 4 , 13 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health-related quality of life (OHRQoL), as a part of general health and well-being, has become very important in dental epidemiological and clinical studies that measure the extent of teeth loss and the impact of dental intervention ( 1 , 2 , 3 , 4 ). A recent study identified 20 Dental Patient-Reported Outcome Measure (dPROM) Questionnaires with multiple items in the English language ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PROs were developed for oral health based on the fact that oral health is an integral part of overall health ( 4 , 5 ). The OHRQoL is thus a predictor of HQoL ( 6 ), such that factors that negatively affect OHRQoL will invariably affect HQoL ( 6 , 7 ). The importance of OHRQoL and dPROs in guiding decisions about the oral health of individuals has been documented ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%